Associated Factors Related to Self-Management Behaviors among People with Type 2 Diabetes in Myanmar - Aye Nyein Oo; Jiraporn Lininger; Sirirat Leelacharas (Makara Journal of Health Research, 2023)
Background: Diabetes is a global health concern that affects individuals and the healthcare system. This study aimed to describe the relationships between personal and environmental factors and self-management behaviors in individuals with type 2 diabetes mellitus (T2DM).